Effect of water depth, seedling age, and day length on elongation induced by short-duration flooding treatment in rice - Dwivedi, J. L.; Senadhira, D.; Singh, P. P.; Jha, G. N.; Verma, O. P. (Universiti Putra Malaysia Press, 1996)
Experiments conducted on seedling age and different water depths revealed that short-duration, 7-day flooding of 3 week- old seedling was effective in assessing elongation potential in deepwater rice varieties. Water depths of 90-100 cm were sufficient to express elongating ability and 3-week-old seedlings gave better contrast between elongating modern varieties and non-elongating modern varieties. Maximum internode length was under short-day-length conditions while shortest internodes were obtained in the long day treatment. Internode elongation may be due only to the signal effect of day length or the shading effect on assimilation. Further experiments should be conducted to confirm these findings.